Effect of IBA concentration and water soaking on rooting hardwood cuttings of black mulberry (Morus nigra L.) - Aziz, Rasul Rafiq; Mohammed, Aram Akram; Ahmad, Faraydwn Karim; Ali, Ari Jamil (Sulaimani Journal for Pure and Applied Sciences, 2020)
The research was conducted at the College of Agricultural Sciences Engineering/University of Sulaimani/ Kurdistan Region-Iraqi to investigate effects of different concentrations of IBA (0, 3000, 4000 and 5000 ppm) and soaking in water for 24 hours on propagation black mulberry (Morus nigra L.) by hardwood cuttings. In this research the parameters of rooting percentage, root number, root length, sprout bud number, shoot length and shoot diameter were measured. Effect of individual factors showed that the highest rooting percentage (15%) was achieved in cuttings soaked in water for 24 hours, as well as improving other traits. Also, the best (23.33%) rooting was found in cuttings dipped in 4000 ppm IBA. Interaction effects of the two factors showed that cuttings treated with 4000 ppm IBA and soaked in water for 24 hours gave the highest (40%) rooting, and the highest other root and shoot traits were achieved in the same interaction as well.
Keywords: Black mulberry; IBA concentration; soaking in water; hardwood cuttings